Developing KASP Markers on a Major Stripe Rust Resistance QTL in a Popular Wheat TAM 111 Using 90K Array and Genotyping‐by‐Sequencing SNPs. Issue 1 (1st January 2019) - Yang, Yan; Basnet, Bhoja R.; Ibrahim, Amir M.H.; Rudd, Jackie C.; Chen, Xianming; Bowden, Robert L.; Xue, Qingwu; Wang, Shichen; Johnson, Charles D.; Metz, Richard; Mason, Richard Esten; Hays, Dirk B.; et al.
Abstract : Stripe rust, caused by Puccinia striiformis Westend. f. sp. tritici Erikss. ( Pst ), is an important disease of wheat ( Triticum aestivum L.) in the United States and many other areas of the world. To identify the genetic basis of resistance in the winter wheat cultivar 'TAM 111', a mapping population of 124 F6 recombinant inbred lines (RILs) developed from the cross TAM 112/TAM 111 was evaluated against Pst populations over eight field environments in the United States and against race PST‐100 in the greenhouse. A high‐density genetic map was constructed using the wheat 90K iSelect array and genotyping‐by‐sequencing (GBS) markers. A set of 6343 markers covering 11.8 Gb of all 21 chromosomes, including 16 simple sequence repeat (SSR) and sequence‐tagged site (STS), 3335 GBS, and 2992 single nucleotide polymorphism (SNP) markers from the 90K array were used for quantitative trait locus (QTL) analyses. Eight QTL on chromosomes 1A, 2A, 2B, 4A, 4B, 6B, and 7D were identified, and two of them were novel. Six tightly linked SNP markers were converted to Kompetitive allele specific polymerase chain reaction (KASP) markers for high‐throughput screening of the largest and most consistent QTL at 154.3 Mb of chromosome 2B. This QTL, QYr.tamu‐2B, was involved with significant epistatic interactions on both disease severity and infection type, and epistasis × environment interactions with QYr.tamu‐2A1 on disease severity only. These QTL can be combined with effective major genes to enhance the stripe rust resistance, and corresponding diagnostic markers can be applied through marker‐assisted breeding.